2019
DOI: 10.3897/biorisk.14.30319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydromorphological pressures on the macrophytes bioindicators of the ecological water quality in Mediterranean rivers

Abstract: One of the important tools to evaluate the ecological quality of surface water is the Macrophytes indices based on the bioindication capacity of aquatic plants. In Mediterranean rivers (France, Spain, and Portugal), the development of some macrophytes indices like l’Indice Biologique Macrophytes Rivières (IBMR), the biological metric score (BMS), as well as the Fluvial Macrophyte Index (IMF) are founded on the determination of the indicator values of the floristic reference lists. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Primary producers are an essential part of aquatic ecosystems, and their role as bioindicators and sensitivity to eutrophication and organic pollution has been extensively studied. In the last decades, there is a growing recognition that flow regime is also a key driver for primary producers in streams and rivers (Abati et al, 2016; Abdellah & Saad, 2019; Bergey et al, 2010; Franklin et al, 2008). The ecological response of primary producers to flow alteration can be identified in terms of changes in biomass and community structure and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Primary producers are an essential part of aquatic ecosystems, and their role as bioindicators and sensitivity to eutrophication and organic pollution has been extensively studied. In the last decades, there is a growing recognition that flow regime is also a key driver for primary producers in streams and rivers (Abati et al, 2016; Abdellah & Saad, 2019; Bergey et al, 2010; Franklin et al, 2008). The ecological response of primary producers to flow alteration can be identified in terms of changes in biomass and community structure and composition.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of the IBMR scores for various Oum Er-rbia river sites indicates that this metric cannot be considered relevant (difference significantly greater than 1). The low values of IBMR and its instability can be explained by a low richness in contributing species (Demars et al, 2012;Maissour and Benamar 2019). Thus, the Oum Errbia river is characterized by the dominance of algal flora, notably Spirogyra sp., Vaucheria sp., and Cladophora sp., which are considered ubiquitous taxa (Nouri et al, 2022), they can grow to the detriment of sensitive species and directly affect the IBMR score (Treguier and Lietout 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The pollutants that come with stormwater can be buried in bottom sediments or accumulate in the tissues of aquatic biota ( Gołdyn et al, 2018 ; Barałkiewicz et al, 2014 ). Many studies have shown that macrophytes are able to significantly reduce the concentration of harmful substances ( Ladislas et al, 2012 ) and be indicators of the quality of the environment ( Kohler & Schneider, 2003 ; Maissour & Benamar, 2019 ). The work of ( Barałkiewicz et al, 2014 ) showed that a reservoir located in the riverbed can contribute to the elimination of pollutans from stormwaters, despite the very short residence time of water in it.…”
Section: Discussionmentioning
confidence: 99%